Religious Basic Idea in Forming Non-Penal Policy to Countermeasures Supporter Anarchism - Laras Astuti; Eko Soponyono; RB Sularto (Media Iuris, 2022)
AbstractThe background of this research is to analyze and formulate an ideal non-penal policy to countermeasures supporter anarchism based on religious values as contained in Pancasila. This is because the problem of supporter anarchism is no longer only solved through institutional punishment but must look for other “punishment” alternatives or “causative treatment” that are more internal in nature so that supporter anarchism can restore themselves and provide support to their football club properly. Especially if the main problem of supporter anarchism is caused by a misperception of understanding the implementation of fair play football, making them unfair and uncivilized supporters. Formulating a non-penal policy can be done as an answer to the weaknesses of the criminal justice system to countermeasures supporter anarchism. The policy will be carried out based on the religious ideas contained in Pancasila which reflects the identity and character of the Indonesian nation. This goal will be achieved by using normative research based on literature and legislation review with an emphasis on secondary data processing. Based on the research, it can be concluded that there are four basic religious ideas that can be used as a basis for countermeasures supporter anarchism, namely the domestication function as a tool to limit, the personalization function as a tool to make good and caring individuals, the compensation function as a tool to limit social conflict, and the function of innovation as a tool creative function to help resolve problems or conflicts. Keywords: Religious Idea; Non-Penal Policy; Supporter Anarchism.